Assessment of nematophagous fungi and neem cake compatibility against Heterodera cajani on cowpea - P.c. TRIVEDI, PREETI BHARADWAJ and (Indian Phytopathology, 2002)
A significant reduction in disease incidence was observed when either Paecilomyces lilacinus or Verticillium chlamydosporium (@ 4 or 8 g) were applied against Heterodera cajani on cowpeas in pot tests. The addition of 4 g neem cake to the lower doseof the fungi helped improve the control effect.